A disability disclosure simulation as an educational tool. Issue 8 (10th May 2020) - Lindsay, Sally; Rezai, Mana; Shen, Winny; Lyons, Brent
Abstract : Purpose: Many employers struggle with how to have a disability disclosure discussion with their employees and job candidates. The primary purpose of this study was to identify issues relevant to disability disclosure discussions. In addition, we explored how simulations, as an educational tool, may help employers and managers. Design/methodology/approach: Seven participants (four employers and three human resource professionals) took part in this study. We used a qualitative design that involved two focus group discussions to understand participants' experiences of building a simulation training scenario that focused on how to have a disability disclosure discussion. The simulation sessions were audio-recorded and analyzed using an open-coding thematic approach. Findings: Four main themes emerged from our analysis. Three themes focused on issues that participants identified as relevant to the disability disclosure process, including: (1) creating a comfortable and safe space for employees to disclose, (2) how to ask employees or job candidates about disability and (3) how to respond to employees disability disclosure. A fourth theme focused on how simulations could be relevant as an educational tool. Originality/value: Developing a simulation on disability disclosure discussions is a novel approach to educating employers and managers that has the potential to help enhance diversity and inclusion in the workplace. Further, the process that we followed can be used as a model for other researchers seeking to develop educational training scenarios on sensitive diversity and inclusion topics.